Telenovela e a identidade feminina de jovens de classe popular - Sifuentes, Lírian (2010)
The aim of this paper was to comprehend how the conflicts and complementarities between the audience of telenovela and other elements of daily life - family, school and social class - form the feminine identity of young women from working class. Cultural Studies are used as theoretical and methodological model, especially as regards the theory of cultural mediation (Jesús Martín-Barbero) and the Encoding and Decoding model (Stuart Hall). The sample was composed of 12 young female aged between 16 and 24 years, residents of the neighborhood Urlândia, outskirts of Santa Maria-RS. The study was a ethnography of the audience and the data collection techniques used are participant observation, with register in a field diary, application of socio-cultural forms, a semi-directed interview and by watching telenovela in interviewers home. The results of this research point to the imposition of social class in the identities of these young women. Material shortage defines the daily life experiences and ways of being a woman, by teenage pregnancy, by the work, by dropping out of school or by television as the main form of recreation. The role of telenovela is also essential, once that, in addition of (re)producing a pattern of gender - that motherhood and marriage are the women s priorities - there is, at least in a scattered way, an ideology of gender equality, which, even problematic, is greater than the reality that surrounds them. Despite this speech hardly result in a practice, it s crucial because it also contributes to the feminine identity construction.